THE EFFECTIVENESS OF EDUCATION AND INFORMATION ON THE ANXIETY LEVEL OF PRE-ELECTIVE SURGERY PATIENTS AT HVA HOSPITAL, PARE, KEDIRI - Eko Dian Hadi Suprayetno; Anik Nuridayanti; Agus Priyanto (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Patients who undergo elective surgery are still anxious about the action that will be carried out when they enter the operating room, even though the surgeon has explained it as the Doctor Responsible for the Patient. The patient's anxiety in the operating room is characterized by frequent questions about the progress of the operation and a lack of cooperation when preparing a series of operations in the operating room. This research used a correlation research type, a Pre-Experimental research design with a population of elective pre-operative patients in the operating room at HVA Kediri Hospital. The total sample was 25 respondents using a sequential sampling technique. The data collection method used a questionnaire. Data were analyzed using the Wilcoxon test. The study results showed that before being given information and education to preoperative patients, almost half, 11 respondents (44%) experienced moderate anxiety. After being given information and education, it was found that the majority did not experience anxiety, 15 respondents (60%). There was a significant difference in anxiety between before and after being given education and information (p-value = 0.000; Î± <0.05). Education and information before the patient undergoes surgery can reduce the patient's anxiety level. Sufficient knowledge regarding the actions to be carried out means that the patient knows and does not ask questions about what will happen to him in the operating room.